STRATEGI MADRASAH IBTIDAIYAH DALAM MENINGKATKAN PROFESIONALISME GURU KELAS DI ERA REVOLUSI INDUSTRI 4.0 - Bela Vita Rismawati; Muhamad Arif; Muhammad Mahfud (Universitas Islam Malang, 2021)
Professionalism for Elementary School / Madrasah Ibtidaiyah teachers is a necessity that must be possessed, in the presentation of professionalism for teachers there are four minimum competencies, namely pedagogic, professional, social and personality. Basically, the discussion about teacher professionalism is actually very clear in the